INSTRUMENTS FOR THE ASSESSMENT OF HEALTH LITERACY IN ADOLESCENTS - Pavić, Katarina; Simin, Dragana (HEALTH CARE, 2024)
Health literacy is defined as an individual's ability to receive, process and understand health information. Adolescence is a key stage of psycho-physical development, and therefore, improving the health literacy of young people would significantly contribute to the adoption of healthy habits and empower them to take control of their own health. The aim of this review article was to present instruments for assessing health literacy in the adolescent population. The identification of instruments for the adolescent population was carried out through a literature search using different databases. Of 9 instruments, which were compared in relation to the domain of measuring health literacy and the method of data collection, six (HLS-Child-Q15, HELiASeSS, HAS-A, HELMA, eHEALS, HLAT-8) assess health literacy in all three domains, and therefore, they can offer a more complete picture of the level of health literacy in adolescents. Of these 6 instruments, HLS-Child-Q15 and HELMA are available for downloading which can influence the greater implementation in the future for the assessment of health literacy in adolescents.
Keywords: health literacy; adolescents; health literacy assessment instruments